Direct Ink Writing of Silicon Carbide for Microwave Optics1. Issue 1 (19th September 2015) - Larson, Chris M.; Choi, Justin J.; Gallardo, Patricio A.; Henderson, Shawn W.; Niemack, Michael D.; Rajagopalan, Ganesan; Shepherd, Robert F.
Abstract : 3D silicon carbide structures are patterned via direct ink writing (DIW) of borosiloxane‐colloidal SiC ink blends. These hybrid inks enable printing over a wide range of colloidal volume fractions (0.38 < ɸ < 0.54) to produce relative densities of ≈30–50%. Structural (bars, cylinders, turbines) and functional (periodic lattices, microwave feedhorns) components are printed and sintered with excellent shape stability. The SiC feedhorns transmit microwaves (8.5 GHz) with very low insertion losses (≈0.05 dB) relative to commercial standards, demonstrating their potential in microwave optics applications.